2002
DOI: 10.1067/mva.2002.120372
|View full text |Cite
|
Sign up to set email alerts
|

Duplex scan–directed placement of inferior vena cava filters: A five-year institutional experience

Abstract: Our experience indicates that duplex ultrasound-directed IVC filter placement is safe, cost-effective, and convenient for patients who need IVC filter placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…The outcomes in this study compare favorably with other published bedside filter experiences, [7][8][9][10][11][12][13][14][15][16][17][18][19] but what is different in this study is the prospective algorithm-driven decision making that supported bedside placement. Furthermore, although other published reports advocate single-or dual-access techniques, the prospective algorithm in this study included a pathway preferring a single-access approach (94.4%) first, reserving dual access (5.6%) for inadequate imaging with single access or if direct visualization of the filter-delivery catheter tip at the renal vein was required.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The outcomes in this study compare favorably with other published bedside filter experiences, [7][8][9][10][11][12][13][14][15][16][17][18][19] but what is different in this study is the prospective algorithm-driven decision making that supported bedside placement. Furthermore, although other published reports advocate single-or dual-access techniques, the prospective algorithm in this study included a pathway preferring a single-access approach (94.4%) first, reserving dual access (5.6%) for inadequate imaging with single access or if direct visualization of the filter-delivery catheter tip at the renal vein was required.…”
Section: Discussionsupporting
confidence: 57%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Because of increasing demands for filter placement at our institution, bedside techniques using IVUS guidance were disseminated according to prior experience levels and a proctored process.…”
Section: Discussionmentioning
confidence: 99%
“…Our 6% incidence of filter malposition is similar to the reported series (0-7%) using double puncture, pullback or single puncture, and single sheath techniques. [1][2][3][4][5][6][7][8][9][10]12 Filter tilt was recorded in only 3 of these institutional series, but we have shown that filter excessive tilt and malpositioning were most prevalent with procedures done via left femoral access and can be minimized with a single puncture, single sheath technique through a right femoral access site. Use of preprocedural duplex ultrasound to evaluate the right common femoral vein is recommended.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4] A bedside procedure using ultrasound imaging is advantageous, especially for the patients in the intensive care unit (ICU), since the risk associated with inhospital transport of critically ill patients is eliminated, as is the need for intravenous contrast or radiation exposure to staff. Bedside procedures can be performed at any time and can avoid scheduling conflicts in the OR or angiography suite.…”
mentioning
confidence: 99%
“…Ultrasound guidance also obviates the need for ionizing radiation and nephrotoxic contrast administration. [2][3][4][5] The techniques described in the literature include guidance with transabdominal US or with a combination of intravascular US (IVUS) and transabdominal US guidance.…”
Section: Discussionmentioning
confidence: 99%